Coartación de la aorta torácica con aneurisma postestenótico. - Hernández Amador, Guillermo; Morandeyra Martín, Ángel; Casanova Arzola, Ramón; Paramo Gómez, Salvador (Revista Cubana de Pediatría, 2023)
Reporte de un caso.